2021
DOI: 10.1200/op.20.00557
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Conversion of a Palliative Care Outpatient Clinic to Telehealth

Abstract: PURPOSE: The coronavirus pandemic has transformed the practice of medicine, forcing a rapid transition to telehealth. As a specialty, palliative care relies upon expert-level communication and interdisciplinary care. We describe the transition of the Dana-Farber Cancer Institute palliative care clinic into a predominantly telemedicine model. RESULTS: We document how we significantly increased goals of care conversations while maintaining patient volume and interdisciplinary care. We present how the components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 5 publications
(4 reference statements)
1
50
0
4
Order By: Relevance
“…The rapid integration of telemedicine into palliative care during the Covid-19 pandemic provides further insight into the use of telemedicine in palliative care and anticipates the important role of telemedicine in post-pandemic palliative care [ 24 , 37 , 38 ]. Therefore, it is worthwhile considering palliative patients’ and relatives’ preferences and concerns in relation to the use of telemedicine in palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid integration of telemedicine into palliative care during the Covid-19 pandemic provides further insight into the use of telemedicine in palliative care and anticipates the important role of telemedicine in post-pandemic palliative care [ 24 , 37 , 38 ]. Therefore, it is worthwhile considering palliative patients’ and relatives’ preferences and concerns in relation to the use of telemedicine in palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of palliative telemedicine, which has been bolstered by the COVID-19 pandemic, might further improve access to these services while decreasing logistical burdens on patients and providers. For example, COVID-19 necessitated an expedient transition to telehealth palliative care at a major US cancer centre and showed an increase in goals of care discussions 82 .…”
Section: Delivery Of Palliative Carementioning
confidence: 99%
“…Nurses, physicians, and mental health providers have expressed concern that the two-dimensional interactions in video conferencing coupled with the loss of physical proximity, presence, and touch depersonalizes care and inhibits the providers' ability to best understand the patient and demonstrate care [16][17][18][19]. In palliative care studies, providers have indicated a reluctance to initiate emotional topics, feeling a need to be physically present with the patient to provide necessary support [20,21]. Reluctance has also been described because providers cannot be sure that patients have adequate privacy in videoconferencing visits [14].…”
Section: Knowledge Gapsmentioning
confidence: 99%